Pharmacy practice in Egypt - Nagy Masry, Pishoy Ragaay; Nikoleishvili, Elza (Caucasus Journal of Health Sciences and Public Health, 2018)
The impact of Arabs on Medicine and Pharmacy on the world cannot be overstated. However, the development in Pharmacy education and practice in Arabic-speaking Middle Eastern countries slowed down and stagnated around traditional curricula and apothecary pharmacy for decades. This recession includes: past and current periods conflict, occupation, social and economical pressures and political instability. As a result level of pharmaceutical education and services in the community and hospital sectors has been poor. Egypt with a population of over 82 million. The college of Pharmacy at Cairo University is considered the oldest pharmacy program in the Middle East, from 1824 AD. There are an estimated 138,000 pharmacists and 60,000 community pharmacies in Egypt (2011). A large vaccine and generic medicine industry has been established. The number of pharmaceutical companies in Egypt is the largest in the region and production covers most of the local consumption. Some of the products are being exported to African, Middle Eastern, and Eastern European countries. Clinical Pharmacy profession is not in forward in Egypt. On a governmental level, there was resistance to create a larger role for pharmacists in health care settings, although there were some attempts to establish hospital and clinical pharmacy departments at the Egyptian Drug Authority and the Ministry of Health to set the grounds for such practice. Current legislation does not offer a clear, detailed, and workable scope of practice, which includes professional and legal requirements. That is reason why Pharmacy practice, like Medication therapy management is not currently widely applied in Egypt. However, Pharmacists from the National Cancer Institute and Children’s Cancer Hospital have the concepts of medication therapy management on the individual patient’s level, and separate from the dispensing process. Yet, many challenges face the pharmaceutical sector in Egypt. Inclusion of clinical pharmacy in pharmacy education and in hospital practice is essential. Also, the pharmaceutical industry needs to expand into the area of active pharmaceutical ingredients manufacturing.